Enhancement of ovulation in goldfish (Carassiusauratus) by a supplementary feed incorporatedwith polychaete worm (Marphysa gravelyi) - Parthiban, F; Christopher, I Maria Michael; Selvaraj, S; Surendraraj, A; Venkataramani, V K (Indian Journal of Fisheries, 2014)
Live feeds play a vital role in the enhancement of growth, maturity in ornamentalfish culture and production of broodstock. An experimental trial was conductedto study the effect of supplementary feed incorporated with locally availablepolychaete worm (Marphysa gravelyi) on feed intake, conversion, coloration andfecundity of gold fish (Carassius auratus). Fishes were fed with polychaete wormincorporated iso-protein feed at the rate of 0%, 5%, 10%, 15% and 20%. Significantgrowth increment was observed between experimental feed and the control (P<0.01). Among the experimental animals fed with polychaete worm incorporatedfeed, more than 80% of them were observed to have matured within a period of60 days. The fecundity was more in gold fish fed with polychaete wormincorporated in the conventional feed at 15% and 20% level.